In silico assessment of drug-Like Properties of Phytocannabinoids in Cannabis Sativa - Desa Shakinaz, Osman Asiah, Hyslop Richard (Universiti Pendidikan Sultan Idris, 2017)
In silico assessment of drug-Like Properties of Phytocannabinoids in Cannabis Sativa by Desa Shakinaz, Osman Asiah, Hyslop Richard,